1993
DOI: 10.3171/jns.1993.79.2.0204
|View full text |Cite
|
Sign up to set email alerts
|

Adult intramedullary spinal cord ependymomas: the result of surgery in 38 patients

Abstract: Thirty-eight patients underwent surgery for an intramedullary spinal cord ependymoma. In 37 patients, postoperative magnetic resonance imaging confirmed that the tumor was totally removed. The morbidity of surgery was directly related to the preoperative neurological condition. Patients who were normal or nearly normal preoperatively were rarely worse after surgery, and those who had significant disability preoperatively were at greatest risk of being more impaired after surgery. There has been no tumor recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
164
1
23

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(194 citation statements)
references
References 16 publications
6
164
1
23
Order By: Relevance
“…Previous single-institution series have almost exclusively focused on the description, prevention and management of neurologic complications. [8][9][10][11][12][13][14] Our study demonstrates the significant negative impact of mostly nonneurologic complications on patient outcomes. Therefore, avoidance, recognition and prompt management of neurologic as well as nonneurologic postoperative complications is extremely important in the successful surgical management of patients with spinal tumors.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Previous single-institution series have almost exclusively focused on the description, prevention and management of neurologic complications. [8][9][10][11][12][13][14] Our study demonstrates the significant negative impact of mostly nonneurologic complications on patient outcomes. Therefore, avoidance, recognition and prompt management of neurologic as well as nonneurologic postoperative complications is extremely important in the successful surgical management of patients with spinal tumors.…”
Section: Discussionmentioning
confidence: 87%
“…Previous single-institution series have reported postoperative complication rates of 11-64% with generally higher complication rates after resection of astrocytomas compared to ependymomas. [8][9][10][11][12][13][14] The NIS data do not afford distinction between the different pathologic types of spinal cord tumors and hence, we cannot comment on the complication rates after resection of astrocytomas versus ependymomas. Furthermore, the 17.5% complication rate we report in our study is likely an underestimate of the true complication rate because only select complications were examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gross total resection (GTR) has been established as the gold standard in the treatment of intramedullary ependymoma, with series reporting 70-100% of ependymomas being radically resected [6,16,20,45,57] and long-term survival being the rule rather than exception. On the contrary, the therapeutical spectrum in infiltratively growing intramedullary astrocytomas ranges from histological verification and decompressive surgery with subsequent radiotherapy [64] to GTR, with 6-70% of intramedullary astrocytomas undergoing GTR [27,28,34,49,56,58,61,64].…”
Section: Introductionmentioning
confidence: 99%
“…11,12,20 ± 23 Mork et al 3 have reported that the 10-year survival rate was no di erent in patients treated with surgery alone than in those with additional radiation therapy. Peschel et al 22 have recommended postoperative radiotherapy for the patients who had both total and subtotal resection, while Epstein et al 24 have advocated that radiation therapy was not a necessary adjunct following gross total removal of the tumor. In our series, seven patients including three patients who had total tumor removal received postoperative radiation; however, at present it is considered to be unnecessary for patients with complete resection.…”
Section: Discussionmentioning
confidence: 99%